Pengaruh Harga, Citra Merek, Positioning Dan Diferensiasi Produk Terhadap Keputusan Pembelian Konsumen Pada Produk Jamu PT. Njonja Meneer - Idham Kurnia Simamora; Handoyo Djoko Waluyo; Widayanto Widayanto (Universitas Diponegoro, 2013)
PT. Njonja Meneer is one of the companies engaged in the herbal industry in Indonesia. Today competition in the herbal industry is highly competitive. Therefore, PT. Njonja Meneer must continue to improve its marketing strategy to the level of consumer purchasing decisions continues to increase. The strategies include the following with concern to product pricing strategies, creating a good brand image, positioning the right, and the diversity of the company's product differentiation. If four things are going well then the automatic level purchasing decisions of consumers will increase. This research aimed to determine the effect of price, brand image, positioning and product differentiation on consumer purchasing decisions on medicinal products PT. Njonja Meneer. The population is not limited to any consumer product that is herbal PT. Njonja Meneer ever made ​​a purchase at Pondok Jamu Njonja Meneer Depok-Semarang, arguing Fraenkel set Wallen sample of 100 people by spreading using the Nonprobability Sampling (Accidental Sampling). Collecting data using interviews with the help of questionnaires that have been through the instrument validity and reliability. Data were analyzed with qualitative and quantitative analysis using the coefficient of determination test, simple and multiple linear regression, cross tables and tests of significance with SPSS 18.0. The results show that variable rates affect consumer purchasing decisions of 36 percent. Variables affect the brand image on purchase decisions of consumers by 23,2 percent. Variable positioning influence consumer purchasing decisions at 38,2 percent. Variable product differentiation affects consumer purchasing decisions at 38,5 percent. Taken together price, brand image, positioning, and product differentiation affect consumer purchasing decisions by 21 percent. The conclusion is the price, brand image, positioning, and product differentiation have a positive and significant impact on consumer purchasing decisions on medicinal products PT. Njonja Meneer as evidenced from the results of the test f count (6.331)> f table (2.309). Bottom line if four factors are balanced the synergism of herbal products Njonja Meneer will get high levels of consumer purchases that will be a positive influence on survival.